Expert System for Diagnosing Damage to Automatic Motorcycle Engines Using the Forward Chaining Method - Nanang Nuryadi; Aziz Setyawan Hidayat; Felix Wuryo Handono; Ayuni Asistyasari; Yosep Nuryaman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Damage to the matic engine due to negligence in treatment. The new vehicle owners aware of the damage after the vehicle can not operate properly. Therefore, the use of vehicles likely to require regular maintenance. By way of detecting damage to what is happening on the vehicle. For example, if the vehicle sound noisy and have no idea why this happens, it is this which encourages the development of an expert system to identify / diagnose matic damage to the engine. Submission of information was carried out using visual basic applications that have been made​​. By running the application diagnosis expert system engine matic damage to the computer, it will be processed in the system then the results will be displayed on the computer screen. This system is expected to provide optimal information from the user and the system of reciprocity.This study is expected to provide all information related to the engine damage problem quickly and efficiently on a reciprocal basis between the user and the system.